2017
DOI: 10.3892/ol.2017.6482
|View full text |Cite
|
Sign up to set email alerts
|

All-trans retinoic acid enhances temozolomide-induced autophagy in human glioma cells U251 via targeting Keap1/Nrf2/ARE signaling pathway

Abstract: The present study evaluated the retinoic acid (RA) enhancement of temozolomide (TMZ) effects on the human glioma cells U251 and explored its underlying molecular mechanism. The cell growth was detected using the MTT assay and the cell cycle was assessed by flow cytometry. Cell apoptosis was analyzed by Annexin V/propidium iodide staining, and the cell morphology was evaluated using transmission electron microscopy (TEM). Additionally, reverse transcription-PCR and western blot analysis were applied to detect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Nrf2 and its downstream genes are highly expressed in many tumor cells (including gliomas) or tissues, and it has a role in promoting tumor growth, proliferation, and drug resistance (69)(70)(71)(72). Numerous studies have shown that Nrf2 also plays an important role in TMZ resistance in gliomas (73)(74)(75). The treatment of glioma cells with TMZ would induce high expression of Nrf2, and the inhibition of Nrf2 expression can increase the sensitivity of glioma cells to TMZ (73)(74)(75).…”
Section: Nrf2 Regulates Ferroptosis In Glioma Tmz Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Nrf2 and its downstream genes are highly expressed in many tumor cells (including gliomas) or tissues, and it has a role in promoting tumor growth, proliferation, and drug resistance (69)(70)(71)(72). Numerous studies have shown that Nrf2 also plays an important role in TMZ resistance in gliomas (73)(74)(75). The treatment of glioma cells with TMZ would induce high expression of Nrf2, and the inhibition of Nrf2 expression can increase the sensitivity of glioma cells to TMZ (73)(74)(75).…”
Section: Nrf2 Regulates Ferroptosis In Glioma Tmz Resistancementioning
confidence: 99%
“…Numerous studies have shown that Nrf2 also plays an important role in TMZ resistance in gliomas (73)(74)(75). The treatment of glioma cells with TMZ would induce high expression of Nrf2, and the inhibition of Nrf2 expression can increase the sensitivity of glioma cells to TMZ (73)(74)(75).…”
Section: Nrf2 Regulates Ferroptosis In Glioma Tmz Resistancementioning
confidence: 99%
“…CMA involvement in TMZ’s mechanism of action has been also proposed by Shi et al [ 68 ], describing LAMP-2A stabilization after treatment with retinoic acid (RA). Indeed, in glioma, it has been shown that RA can support TMZ’s cytotoxic effect by improving autophagic induction and blocking cell proliferation in U251 glioma cells [ 68 ].…”
Section: Cma In Gliomamentioning
confidence: 78%
“…All-trans-retinoic acid has been used to treat glioma cells as it has been shown to significantly inhibit the proliferation of glioma cells and induce apoptosis. [23] Moreover, retinoic acid improves the pro-apoptosis effect of temozolomide on U251 cells via the Kelch-like ECH-associated protein 1-nuclear factor erythroid 2-related factor 2-antioxidant response elements signaling pathway, [24] which suggests that the retinoic acid signaling pathway possesses a strong inhibitory effect on proliferation of glioma at the cellular level. Recently, it has been shown that RDH10 is expressed in non-small cell lung cancer, mainly grade III disease, suggesting that it has a very important role in the development of this cancer.…”
Section: Discussionmentioning
confidence: 99%